The ER transmembrane protein PGRMC1 recruits misfolded proteins for reticulophagic clearance. Issue 1 (2nd January 2022) - Knupp, Jeffrey; Chen, Yu-Jie; Arunagiri, Anoop; Haataja, Leena; Arvan, Peter; Tsai, Billy
ABSTRACT: ER-specific autophagy (reticulophagy) has emerged as a critical degradative route for misfolded secretory proteins. Our previous work showed that RTN3 (reticulon 3) drives reticulophagic clearance of disease-causing mutant prohormones. How RTN3, a protein residing on the cytosolic leaflet of the ER bilayer, recruits these lumenally-localized cargos has remained a mystery. To address this question, we used an unbiased proteomics approach to identify RTN3-interacting partners. We discovered that RTN3 recruits misfolded prohormones for lysosomal degradation through the ER transmembrane protein PGRMC1. RTN3 complexes with PGRMC1, which directly binds to misfolded prohormones via its distal ER lumenal domain. Cargos for the RTN3-PGRMC1 degradative axis include mutant POMC (proopiomelanocortin) and proinsulin, each of which oligomerizes in the ER during misfolding, entrapping their wild-type counterparts, leading to secretion defects. Although reticulophagy is thought to degrade large protein aggregates, PGRMC1 instead selectively recruits and promotes degradation of only small oligomers of the mutant prohormones. Of physiological importance, genetic or pharmacological inactivation of PGRMC1 in pancreatic β-cells expressing both wild-type and mutant proinsulin impairs mutant proinsulin turnover and promotes trafficking of wild-type proinsulin. These findings pinpoint PGRMC1 as a possible intervention point for diseases caused by ER protein retention.